2018
DOI: 10.1182/blood-2018-02-834721
|View full text |Cite
|
Sign up to set email alerts
|

Temporal autoregulation during human PU.1 locus SubTAD formation

Abstract: Abstract Epigenetic control of gene expression occurs within discrete spatial chromosomal units called topologically associating domains (TADs), but the exact spatial requirements of most genes are unknown; this is of particular interest for genes involved in cancer. We therefore applied high-resolution chromosomal conformation capture sequencing to map the three-dimensional (3D) organization of the human locus encoding the key myeloid transcription factor PU.1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Suspecting that this region might reside in close proximity to the proximal Ϫ60-bp region as a consequence of chromatin looping, we next investigated the contribution of LDB1. Since this factor has been shown to facilitate chromatin loop formation of the genes regulated by the GATA factors or PU.1 (27)(28)(29)(30), we speculate that the ϩ10.4-kbp and Ϫ60-bp regions were bound by LDB1. As expected, ChIP-qPCR analysis revealed that the ϩ10.4-kbp and Ϫ60-bp regions were bound by LDB1 in BMMCs and that PU.1 ablation significantly reduced the binding activity (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Suspecting that this region might reside in close proximity to the proximal Ϫ60-bp region as a consequence of chromatin looping, we next investigated the contribution of LDB1. Since this factor has been shown to facilitate chromatin loop formation of the genes regulated by the GATA factors or PU.1 (27)(28)(29)(30), we speculate that the ϩ10.4-kbp and Ϫ60-bp regions were bound by LDB1. As expected, ChIP-qPCR analysis revealed that the ϩ10.4-kbp and Ϫ60-bp regions were bound by LDB1 in BMMCs and that PU.1 ablation significantly reduced the binding activity (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Furthermore, LDB1 appeared to be a novel positive regulator of Ms4a2 gene expression according to KD studies. Interestingly, a recent study reported that PU.1 plays an essential role in the formation of the chromosome architecture during SPI1 gene autoregulation by recruiting LDB1 in human monocytes (30). Recent Hi-C experiments revealed that eukaryote chromatin is organized into compartments composed of topologically associating domains (TADs) that are critical chromosome structural domains in the regulation of long-range gene expression (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, overexpression or ablation of key TFs results in cell fate changes [46]. Once established, lineage choice is often reinforced by autoregulatory circuits [47,48].…”
Section: Transcription Factors In Mds and Amlmentioning
confidence: 99%
“…It is orchestrated by precise spatiotemporal expression of the hematopoietic master regulator PU.1 [1][2][3][4] . PU.1 gene expression is regulated through enhancer-promoter interactions within a topologically associated domain (TAD) 5,6 . PU.1 levels increase during myeloid differentiation while failure to do so results in myeloid leukemia 7 .…”
mentioning
confidence: 99%